Start performance in ski cross und snowboard cross: Influence on race result and kinematic and kinetic analysis - Olvermann, M.; Frühschütz, H.; Goll, M.; Blanz, F.; Reisinger, S.; Huber, A.; Spitzenpfeil, P. (Science and Skiing VII, 2018)
The results confirm the findings of Argüelles et al. (2011) that the start in SX and SBX has a significant influence on the result of the race. It is very important to be in the leading positions at the end of the first race section for a successful race. To improve their performance, athletes should focus on special start training. In a study with a realistic starting area and good standardized conditions, recommendations on key factors for an effective start could be developed. As expected, the start is more effective if the athlete is able to generate a high force value during the pull phase. Besides good strength ability, each athlete should focus on an optimal body position for a good power transmission during the start. The possible influence of the constitution and gender of the athletes is still questionable due to the small number of subjects. However, the coaches can implement these recommendations in the training routine and are able to offer their athletes an effective start training. In this context, one possibility could be a feedback training, where the athletes can get quick information about the relevant parameters, which they are working on.